FIKIH HAM DAN HAK KEBEBASAN BERIBADAH MINORITAS DZIMMI DI INDONESIA - M. Alifudin Ikhsan (Universitas Negeri Malang, 2017)
Abstract: Indonesia is a multicultural country. There are various religions, tribes, cultures and customs. This diversity is a necessity that must be lived as a force in building the country. However, the diversity is tested by various discriminatory events. One is the freedom to worship religious minorities in the midst of a particular religion. The establishment of places by minority religions in various regions continues to reap the controversy. Maturity of the thinking of the majority becomes an important part in realizing the balance of social relations. Therefore, this article tries to realize a new idea of Fiqh HAM. The results of the Qur'anic conception are poured in the idea of human rights fiqh that seeks to build equal rights of worship for citizens. Fiqh HAM is expected to create public awareness to respect and respect the activities of minority worship Abstrak: Indonesia merupakan negara multikultural. Terdapat berbagai agama, suku, budaya dan adat istiadat. Keberagaman ini merupakan sebuah keniscayaan yang harus dijalani sebagai kekuatan dalam membangun negara. Namun, keberagaman itu seolah diuji dengan berbagai peristiwa diskriminasi. Salah satunya adalah kebebasan beribadah kaum minoritas agama di tengah mayoritas suatu agama tertentu. Pendirian rumah ibadah oleh agama-agama minoritas di berbagai daerah terus menuai kontroversi. Pendewasaan pemikiran umat mayoritas menjadi bagian penting dalam mewujudkan keseimbangan hubungan sosial. Oleh karena itu, Artikel ini mencoba untuk mewujudkan gagasan baru mengenai Fikih HAM. Hasil konsepsi Al-Quran tersebut dituangkan dalam gagasan fiqih HAM yang berupaya untuk membangun kesetaraan hak beribadah bagi warga negara. Fiqh HAM diharapkan mampu membentuk kesadaran masyarakat untuk menghargai dan menghormati aktivitas peribadatan kaum minoritas DOI : http://dx.doi.org/10.17977/um019v2i12017p034